The Prohibition of Civil Servant (ASN) in Actions to Benefit Prospective of Regional Head in Public - M Hary Rubianto; Ardiansyah Ardiansyah; Bagio Kadaryanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
This research aims to understand the correlation between ASN and Regional Head Election (Pilkada) as election for choose leader by democratic based on principle of direct, general, free, confidential, honest and fair which submitted by party political or combined party political. About implementation, right choose of Civil Servant or abbreviated with ASN prohibited to declare openly to public to invite choose one of candidate so that tend becomes form